Program Development at the Records Management: Records Management Capacity Assessment System - Külcü, Özgür; Uzun Külcü, Hande (Information World, 2009)
The evaluation of the institutional condition is so important to create effective and continuous systems and analysis of the existing capacity in administrative bodies and records management applications is regarded as crucial. Within this respect, an evaluation of both international and national and an analysis of the existing conditions in records management are necessary. In this study, the programs that were developed for records management and Records Management Capacity Assessment System are evaluated order to identify the conditions and problems in institutional records management.
Keywords: Records management; Software; Evaluation; Performance Measures